Pengaruh Relaksasi Otot Progresif Terhadap Tingkat Stres Narapidana Wanita di Lapas Kelas IIA Jember (The Effect of Progressive Muscle Relaxation on Women Prisoners’s Stress Levels at Prison Class IIA Jember) - Zulfa Makhatul Ilmi; Erti ikhtiarini dewi; Hanny Rasni (Pustaka Kesehatan, 2017)
Women prisoners have a high risk of stress because of the detention of their social life,environment, and behavior. Stress is tensions caused by physical, emotional, social, economic,employment or circumstances, events, or experiences that are difficult to manage or defend. Stresswill increase sympathetic nervous system that causes increased muscle tension, blood pressure,dizziness, indigestion, fatigue, anxiety, anger, and fear. Progressive muscle relaxation is one of thestress management to reduce stress levels. The purpose of this study to determine the effect ofprogressive muscle relaxation against stress levels of women prisoners. Design of the study is apre-experimental with one group pretest-posttest. Samples were taken using a total sampling of 16respondents. Progressive muscle relaxation was given 6x a week for 25-30 minutes. Data weretaken using DASS questionnaire. Data were analyzed using paired t-test. The results obtained frompaired t-test on stress levels is p=0.009. We can conclude that there is a progressive musclerelaxation effect on stress levels of women prisoners in Prisons Class IIA Jember. Suggestions fromthis study were nurses can provide education and training progressive muscle relaxation techniquesfor women prisoners. Progressive muscle relaxation can also be used as a therapy program toreduce stress levels on woman prisoners.Keywords: stress, progressive muscle relaxation, woman prisoners